KAJIAN MANAJEMEN SUMBERDAYA AIR TANAH UNTUK PENINGKATAN PRODUKTIVITAS PERTANIAN DAERAH BALAI GURAH, KECAMATAN IV ANGKAT CANDUNG, KABUPATEN AGAM, PROVINSI SUMATERA BARAT - Jana Hafiza; Fachrul Rozi Ramadhan (Rang Teknik Journal, 2024)
Mapping (exploration) and distribution of groundwater can be described vertically – horizontally. The distribution of rock formations storing/carrying water (permeable) is called an aquifer. Aquifers are strongly influenced by the degree of porosity and permeability of the rock. To obtain an aquifer, a study of geophysical studies needs to be carried out, namely the estimation of geoelectric resistivity, estimation to study the physical properties of rocks against electric currents. The implementation of the research was using three stages of the method; the first stage evaluates geological maps, hydrological maps, groundwater basin maps, topographical maps, and identifies groundwater conditions; the second stage is to explore and map resources, collect physical and chemical properties of water, and evaluate the condition of regional infrastructure at Balai Gurah; the third stage is evaluation and interpretation of exploration results, presenting a map of potential water resources, and evaluating water availability. Based on the CAT map, the flow capacity in the study area can reach 5 L/s, while in springs it can reach 100 L/s. In addition, the layer of shallow wells can reach 7-15 m and deep wells can reach 50m. Groundwater in the Balai Gurah area is greatly affected by changes in the wet and dry seasons. The results of shallow well measurements show that the position of the water varies with a depth of 1-15 m and a body thickness of 20 cm to 2 meters. The results of resistivity measurements indicated that there is a subsurface layer at a depth of 5m and also found the potential for deep groundwater at depths of up to 10m.Keywords: Groundwater, Aquifer, Geo-electricity, Hydrogeology, Agriculture, Water resources